Averting a malaria disaster in Africa--where does the buck stop? - Whitty, Christopher J. M. (World Health Organization, 2004)
The serious threat posed by the spread of drug-resistant malaria in Africa has been widely acknowledged. Chloroquine resistance is now almost universal, and resistance to the successor drug, sulfadoxine-pyrimethamine (SP), is growing rapidly. Combination therapy has been suggested as being an available and potentially lasting solution to this impending crisis. However, the current cost of combination therapy, and especially that of artemisinin combination therapy (ACT), is potentially a serious drawback, even if a significant part of its cost is passed on to the end-user. If the question of cost is not successfully addressed this could lead to adverse results from the deployment of combination therapy as first-line treatment. These adverse effects range from an increase in potentially fatal delays in infected individuals presenting to medical services, to exclusion of the poorest malaria sufferers from receiving treatment altogether. Urgent steps are needed to reduce the cost of combination therapy to the end-user in a sustainable way if it is to be usable, and some possible approaches are discussed.